Pembuatan bio-briket dari produk pirolisis biochar cangkang kelapa sawit sebagai sumber energi alternatif - Rina Novia Yanti; Ambar Tri Ratnaningsih; Hanifah Ikhsani (Universitas Lancang Kuning, 2022)
Fossil fuel sources are non-renewable energy sources and someday will experience scarcity due to the increasing population; it is necessary to look for alternative fuels. Several renewable energies that can replace fossil fuels are water, solar energy, wind, thermal energy, and biomass energy. One biomass energy from plantations is biomass from oil palm plantation waste. Riau Province is Indonesia's largest palm oil producer, with a total land area of ​​2.89 million until 2021. The results of harvesting coconuts will produce waste, i.e., oil palm shells. Oil palm shells can be treated with pyrolysis technology. In the pyrolysis process, three products are produced: liquid, solid (biochar), and oil products (bio-oil). In this study, the pyrolysis product of oil palm shell waste in the form of biochar was used as raw material to produce bio-briquettes. Producing bio-briquettes resulted from pulverized biochar pyrolysis, mixed with tapioca flour adhesive with a percentage of 4% and 8%. Then, the biochar mixture with adhesive was put in a mold and compressed. The results of the bio-briquettes were tested for water content, ash content, volatile matter content, and calorific value. The test results were compared with the Indonesian National Standard (SNI) No. 01-6235-2000. The research results on bio briquettes from the pyrolysis of palm oil shell waste showed the best results at 4% reactant content with 4.45% water content, 5.1% ash content, volatile matter content 40.40%, and the calorific value was 5,999.93 cal/gram.